RENDEMEN DAN KUALITAS CUKA KAYU DARI KULIT TIGA JENIS MERANTI (Shorea spp.) - Trisnu Satriadi (Universitas Lambung Mangkurat, 2012)
This research aims to know yields and quality of wood vinegar of waste logging. Waste logging as material in this research are bark of three species shorea, there are red shorea, yellow shorea and white shorea. The kiln operated for sixth hour. Results revealed that the kiln turned out as much as 7.61 – 7.76% of wood vinegar. Quality of wood vinegar with parameters: color, odor, density, moisture content, and transparency in accordance with the quality standards of wood vinegar from Japan. However, the pH parameter is outside the standard. Chemical components in wood vinegar and the possibility of its use can be analyzed later.